Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.2 - Negative Exponents and Scientific Notation - Exercise Set: 29

Answer

$m^{11}$

Work Step by Step

$\frac{(m^{5})^{4}m}{m^{10}}=\frac{m^{5\times4}\times m}{m^{10}}=\frac{m^{20}\times m}{m^{10}}=\frac{m^{20+1}}{m^{10}}=\frac{m^{21}}{m^{10}}=m^{21-10}=m^{11}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.